Mobilizing Risk Capital to Unlock the Global Potential of Geothermal Power - La Rocca, Roberto; Johansen, Peter; Berman, Laura; Jayawardena, Migara (World Bank, Washington, DC, 2017)
Geothermal heat is increasingly being used around the world to produce electricity in an environmentally friendly way. Current technology could potentially produce more than 70 GW of power, but only about 15 percent of that capacity is currently developed and operating. Most of the high-temperature geothermal resources that are suitable for power generation are located in areas along the global Ring of Fire, a string of volcanoes and seismic areas that stretches 25,000 miles across the globe. It extends from the Indonesian archipelago through New Zealand, the Philippines, and Japan; along the western coast of the Americas and the Caribbean; and through the Rift Valley in Africa, stretching toward Europe. Geothermal power can be very reliable. Because it is non-intermittent and has relatively low operational costs, it is an ideal option for generating base load power. Geothermal power can also serve as a hedge against the volatility of commodity prices, stabilizing systems costs and improving generation mixes. Geothermal produces a small fraction of the carbon dioxide produced by burning fossil fuels. When developed in line with industry standards, it can also provide significant local environmental benefits by offsetting generation options such as coal or diesel, which produce more pollution.